Deskripsi Hasil Belajar Matematika Siswa Pada Materi Sistem Persamaan Linear Tiga Variabel di Madrasah Aliyah Al-Falah Limboto Barat - Wa Ade; Evi Hulukati; Siti Zakiyah (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article discusses the description of students' mathematics learning outcomes on the material of a three-variable system of linear equations. This descriptive research was conducted at Madrasah Aliyah Al-Falah Limboto Barat in the 2021/2022 academic year. The instrument used in this study was a description test or essay test to obtain data on students' mathematics learning outcomes in solving math problems on a three-variable system of linear equations viewed from 4 indicators. The results showed that the average student learning achievement in mathematics reached 62.20% and was categorized as low. The average percentage of student learning outcomes on the knowledge indicator is 91.93%, the understanding indicator is 90.18%, the implementation indicator is 63.50%, and 7.40% for the analysis indicator.